2012
DOI: 10.1107/s0909049512038599
|View full text |Cite
|
Sign up to set email alerts
|

T-REX: new software for advanced QEXAFS data analysis

Abstract: New approaches to analyze the data generated by modern time-resolved X-ray absorption spectroscopy instrumentation are presented as part of a new analysis software to handle files containing typically a few thousand EXAFS spectra. Various filter techniques to remove high-frequency noise and run-away values are discussed as well as advanced analysis tools like linear combination fitting, EXAFS fitting, principal component analysis and phase-sensitive detection. These techniques were implemented in a user-friend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…QEXAFS allows for a fast data acquisition in the subsecond range under realistic in situ conditions. The application of MES on QEXAFS improves the signal-to-noise ratios without losing time or energy resolution, which makes this approach attractive for relatively fast reactions. In that example, a principal component analysis (PCA) revealed two distinct regimes (heating and ignition) within the full modulation period . Later, Ferri and co-workers published phase-resolved spectra of noble-metal catalysts during the catalytic oxidation of CO and the reduction of NO by CO. These studies showed the potential of MES for XAS as it drastically increased surface sensitivity and ultimately formed the basis to study working catalysts, even at low metal loading, that have been previously intractable for dynamic in situ studies.…”
Section: Mes Applicationsmentioning
confidence: 99%
“…QEXAFS allows for a fast data acquisition in the subsecond range under realistic in situ conditions. The application of MES on QEXAFS improves the signal-to-noise ratios without losing time or energy resolution, which makes this approach attractive for relatively fast reactions. In that example, a principal component analysis (PCA) revealed two distinct regimes (heating and ignition) within the full modulation period . Later, Ferri and co-workers published phase-resolved spectra of noble-metal catalysts during the catalytic oxidation of CO and the reduction of NO by CO. These studies showed the potential of MES for XAS as it drastically increased surface sensitivity and ultimately formed the basis to study working catalysts, even at low metal loading, that have been previously intractable for dynamic in situ studies.…”
Section: Mes Applicationsmentioning
confidence: 99%
“…With third-generation synchrotrons, wigglers and undulators, numerous advanced XAFS beamlines can provide very high fluxes across central energy ranges. If samples are stable under this flux density and this is then complemented by very high detector linearity and very fast stable detectors (Stö tzel et al, 2012;Lutzenkirchen-Hecht & Frahm, 2001), then (intrinsic) standard errors can be reduced by a factor of ten or so, or alternatively the counting time can be reduced by 100 or 1000, whether for dynamic investigations or simple throughput.…”
Section: Q2xafs Workhopmentioning
confidence: 99%